Trends in the administration of COVID-19 vaccines with other vaccines in the United States reported to V-safe during December 14, 2020—May 19, 2023 - Casey E. Parker; Anne M. Hause; Paige Marquez; Bicheng Zhang; Tanya R. Myers; David K. Shay (Human Vaccines & Immunotherapeutics)
Introduction COVID-19 vaccines may be administered with other vaccines during the same healthcare visit. COVID-19 monovalent (Fall 2021) and bivalent (Fall 2022) vaccine recommendations coincided with annual seasonal influenza vaccination. Data describing the frequency of the co-administration of COVID-19 vaccines with other vaccines are limited. Methods We used V-safe, a voluntary smartphone-based U.S. safety surveillance system established by the CDC, to describe trends in the administration of COVID-19 vaccines with other vaccines reported to V-safe during December 14, 2020 – May 19, 2023. Results Of the 21 million COVID-19 vaccinations reported to V-safe, 2.2% (459,817) were administered with at least 1 other vaccine. Co-administration most frequently occurred during the first week of October 2023 (27,092; 44.1%). Most reports of co-administration included influenza vaccine (393,003; 85.5%). Co-administration was most frequently reported for registrants aged 6 months-6 years (4,872; 4.4%). Conclusion Reports of co-administration to V-safe peaked during October 2023, when influenza vaccination most often occurs, possibly reflecting increased opportunities for multiple vaccinations and greater acceptability of the co-administration of COVID-19 vaccine with other vaccines, especially influenza vaccine.